A estranha arte de envelhecer longe da pátria: o cotidiano de imigrantes espanhóis atendidos pela Sociedade Beneficente Rosalia de Castro - São Paulo - 2001 - Barroso, Áurea Eleotério Soares (2002)
The present digression analyses the peculiarities of an aging group of Spanish immigrants who are cared of by the Sociedade Beneficente Rosalia de Castro. We consider the that there is not only one way to grow old, and that the aging needs to be cleared up from whom who is daily living and subjectivising this process. The methodology adopted focused both the quantity and the quality and, it comprehended five experimenters out of a quantitatively representing group. A research was made on the files of the institution with the scope of understanding the profile of the researched matter as well as data were collected on the Spanish immigration both at the Consulate of Spain and at the Immigrant's Memorial, both localized in São Paulo City. Furthermore, interviews were made both with the Technician and the Vice-President of the institution, as well as with two social workers; with the Consul of Spain and, with a researcher of the Immigrant's Memorial. Such procedures were materialized with the researcher”s participating observations. The analysis of the information was materialized by means of an hermeneutical hearing, with the scope of understanding what aging represents to a growing old man away from his country that is aged over 65 years, that is an Spanish immigrant, with low economic resources, that resides in the State of São Paulo and, that is cared of by the Sociedade Beneficente Rosalia de Castro.How his growing old affects his life, his sociability and his affection. At last, one tried to reflect about the growing old process of such old men, about the importance of the assembled memories of the roots of their native country, for reassertment of their needs of appurtenance. An analysis of the oral statements was done from a theoretical reference. We based it on the following researchers: Simone de Beauvoir (1990), Maurice Halbwachs (1990), Elisabeth Mercadante (1997) et al. The narratives of the old men reveal that the loss of their native country is an harrowing experience and, that the affective link with their native country does not rip up with the passing years and, the desire of continuing to belong to the affective community of origin stimulates them to look for spaces where the memories of a group member can echo on those of other members. Consequently, they can remember the past and, reconstruct it. A past which allows the temporal continuity of their being. Therefore, the events of the past still keep on existing in the present and, they can be re-appraised over again in future